Macroprudential policies and dollarisation: Implications for the financial system and a cross-exchange rate regime analysis - Fisnik Bajrami (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Macroprudential policy has gained prominence for promoting financial stability. In this paper, we assess the effectiveness of macroprudential policy in reducing credit growth over a 22-year period across 129 countries. Additionally, we investigate the interaction between macroprudential policy, dollarisation, and various exchange rate regimes, examining their impact on different financial stability indicators. Our findings indicate that macroprudential policy significantly reduces credit growth within a quarter of implementation, though this is not evident in the case of soft peg exchange rate regimes. Furthermore, our analysis reveals that dollarised countries exhibit superior outcomes in financial stability when compared to alternative exchange rate regimes.
Keywords: E42; E52; E58; 330; macroprudential policy; dollarisation; exchange rate; credit growth; non-performing loans; inflation; interest rates; empirical evaluation